IMPLEMENTATION OF LAW NUMBER 6 OF 2014 ON VILLAGES RELATED TO THE POLITICAL PARTICIPATION OF WOMEN IN VILLAGE REGULATION IN INDONESIA - Ani Purwanti; Fajar Ahmad Setiawan (Yustisia Jurnal Hukum, 2020)
This article explores the affirmative action related to women's political participation in the village's decision-making process that results in village regulations. This article uses a law-based approach, it will also demonstrate the contrasting implications between affirmative action on the village legislative system and the regional parliamentary system (city, province, and state). The decision-making process in the village differs from the conventional Parliament, where the implications of the affirmative action of village law differ from the parliamentary system. This is due to the existence of the village deliberation where a group of women is mandated to be directly involved in direct deliberation. This feature facilitates bottom-up politics for gender equality and advocacy of women's rights in decision-making where female and group representatives can work shoulder-to-shoulder and safeguard one another on the agenda of Women's empowerment and gender equality. This is a unique advantage that does not exist in parliamentary politics because the quota system does not guarantee the representation of women ideologically in line with the interests of women they represent.